Matlab based simulation model of standalone DC Microgrid for Remote Area Power Applications - Srinivasa Rao, G; Harinadha Reddy, K; Ravi Teja, B; Devasahayam, B; Khaleel, Shaik (International Journal of Engineering and Technology, 2018)
DC microgrids are playing an important role in remote area power applications like power supply to off-grid tele communication towers, off-grid data centres, rural electrification etc. and moreover these are extensively used, as these appear as solutions for integrating two or more renewable energy resources. In this paper, photovoltaic (PV) and wind energy systems have been integrated along with batteries and a load to form an autonomous DC microgrid with high reliability and stability.Â The primary aspects which are to be taken into consideration in a standalone DC microgrid are voltage regulation, load sharing and battery management. In this paper, an energy management strategy is proposed which includes maximum power point tracking (MPPT) algorithms and voltage droop control method. This strategy ensures optimal power sharing among the sources and increases reliability and stability profile of the microgrid. The operation of the microgrid in different modes and the behaviour of the system at different operating conditions is studied by varying the solar irradiance and wind speed for specific time periods. The simulation is done in Matlab Simulink software and the results are obtained.Â